(untitled) (TERRA LATINOAMERICANA, 2024)
Arbuscular mycorrhizal fungi (AMF) and dark septate endophytes (DSEF) have such an influence on plant development and on the edaphological characteristics and nutrients available in the soil that changes in these communities can drive modifications in the biotic and abiotic variables of an ecosystem, demonstrating the synergetic between species. Given its relevance, the objective of this work was to determine the status of colonization in the roots of three representative herbaceous species of the understory of a community of Abies religiosa (Kunth Schltdl. et Cham.) and Pinus harwegii (Lindl), and to contrast the coexistence of colonizers in three conservation-disturbance scenarios that exemplify the vulnerability situations of a forest ecosystem. A tripartite AMF-HESO-plant interaction is reported by the occurrence of coenocytic hyphae, vesicles, septate hyphae, moniliform cells, and sclerotia. The values of arbuscular mycorrhization exceed 50% and are higher than those found for endophytes (15.7-64.5%). The colonization of both types of fungi, such as AMF sporulation (687 spores 50 g-1 soil in the reforested area), seems to be related to the microclimatic conditions resulting from soil use. The edaphological variables that allow inferring the colonization behavior correspond mainly to available phosphorus, calcium, pH, organic matter, and cation exchange capacity. It is concluded that soil properties, its use, and the type of plants are determinant in the establishment of fungal communities. However, more studies on HESO-plant interaction are needed.